Design and Development of Android-Based Indoor Wi-Fi Site Survey Application - Taruna, Ida Bagus Kade; Suarjaya, I Made Agus Dwi; Pratama, I Putu Agus Eka (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
In the indoor wireless network technology, it is found that there are many disturbances such as interference with LOS (Line of Sight), improper access point position, and low signal strength. To overcome these disturbances, wireless network optimization can be done by conducting a survey or analysis of the coverage area and quality of service. This analysis can be done by using an application, however available applications are mostly desktop applications, which makes surveying the indoor wireless network less efficient. This study discusses the design and development of mobile applications that can be used to analyze Wi-Fi networks in an indoor environment which can provide information about the coverage area of ??a Wi-Fi network. The application development uses the PDR (Pedestrian Dead Reckoning) RSSI (Receive Signal Strength Indicator) classification method. Application testing was carried out using two different scenarios, where in the first scenario the Wi-Fi network source was placed in the living room area, while in the second scenario the Wi-Fi network source was placed in the bedroom area 2. The result of the test carried out is the application can provide information regarding the coverage area of the signal from the two positions of different Wi-Fi network sources in a heatmap format that can be easily understood and can be used to optimize Wi-Fi networks in the future. Keywords : Android Application, Wireless Network, Sensor, Network Survey